Claudins Overexpression in Ovarian Cancer: Potential Targets for Clostridium Perfringens Enterotoxin (CPE) Based Diagnosis and Therapy - English, Diana P. (Molecular Diversity Preservation International (MDPI), 2013)
Claudins are a family of tight junction proteins regulating paracellular permeability and cell polarity with different patterns of expression in benign and malignant human tissues. There are approximately 27 members of the claudin family identified to date with varying cell and tissue-specific expression. Claudins-3, -4 and -7 represent the most highly differentially expressed claudins in ovarian cancer. While their exact role in ovarian tumors is still being elucidated, these proteins are thought to be critical for ovarian cancer cell invasion/dissemination and resistance to chemotherapy. Claudin-3 and claudin-4 are the natural receptors for the Clostridium perfringens enterotoxin (CPE), a potent cytolytic toxin. These surface proteins may therefore represent attractive targets for the detection and treatment of chemotherapy-resistant ovarian cancer and other aggressive solid tumors overexpressing claudin-3 and -4 using CPE-based theranostic agents.